EFEKTIVITAS MEDIA DIORAMA TIGA DIMENSI DALAM PEMBELAJARAN ILMU PENGETAHUAN ALAM KELAS IV MA’HAD AL-ZAYTUN 2023 - Mutmainah, Janah; Peranginangin, Henri; Humaeroh, Iis (Cahaya Ilmu Bangsa Institute, 2024)
The purpose of this study was to determine the effectiveness of students' abilities in science learning after the application of three-dimensional diorama media. The research method used is quantitative method with quasi-experimental design. The population in this study was all MI class IV students and the sample used was grade 4-B05 students. Three-dimensional diorama media is an independent variable, while the effectiveness of science learning is a dependent variable. The instrument used is a test in the form of multiple-choice questions. The data obtained were analyzed using inferential statistics using t-test poolled variants. The results of this study show that three-dimensional diorama media fails to reject effectiveness in science learning. This can be seen from the average pretest and posttest results of the class. That is the average postest of 86.46 > the average pretest of 35.03 with an increase in posttest of 51.41. This is reinforced by the results of the hypothesis test using the –t test (t-test). Based on the results of the t-test calculation data, it was obtained that T_hitung = 13.4 and T_tabel = 1.724 So that T_hitung> T_tabel then H0 rejected and Ha failed to refuse. And the average N gain score of the experimental class (using three-dimensional diorama media) is 80.10% included in the effective category. Based on these results, it can be concluded that the use of three-dimensional card diorama media is effective in learning science grades 4-B05 Madrasah Ibtidaiyah Ma'had Al-Zaytun. Keywords: three-dimensional diorama media, effectiveness, science